Prevalence of malaria parasites among blood donors in Kaduna, Nigeria - Garba, Douglas D.; Ameh, Joseph B.; Whong, Clement M. Z.; Aminu-Mukhtar, Maryam (International Journal of Research in Medical Sciences, 2017)
Background: Transmission of malaria parasites through blood transfusion is a well-known serious risk. Screening of blood donors for malaria as recommended by WHO is currently not included in the protocols of many Nigerian blood banks. Presence of asymptomatic Plasmodium species carriers (APCs) in some northern parts of the state has already been demonstrated using rapid diagnostic tests (RDTs) and microscopic examination of Giemsa stained blood films. This research was undertaken to determine the prevalence of malaria parasites among blood donors in Kaduna state, Nigeria. Methods: A cross sectional study was conducted among the blood donors in the three selected Hospitals of Kaduna state. A well-structured questionnaire was used to collect the data regarding demographic profile. Written informed consent was obtained and questionnaire was completed by respondents selected through simple random sampling. 360 blood donors were tested for malaria parasites through microscopic examination of Giemsa stained thick and thin blood films. The data were analysed using Statistical analysis system (SAS) and statistical software for social sciences (SPSS) version 20. Results: A total of 27 (7.5%) of the blood donors had malaria parasites in their blood. Plasmodium falciparum was the only malaria parasite species encountered. There were no mixed infections and no other blood parasites were observed. The prevalence of malaria parasites in the blood donors was significantly associated with occupation (c2=24.0845, df=6, p= 0.0005) and blood group (c2=10.589, df=4, p= O.032). The infected subjects had parasites densities of between 88-250 parasites/µl with a mean parasite density of 126 parasites/µl of blood. Conclusions: The prevalence of malaria parasites among blood donors was 7.5% Blood donors should be routinely screened for malaria parasites and the blood marked negative or positive as the case may be. Recipients of malaria parasites positive blood should be given prophylactic treatment to prevent transfusion related malaria (TRM).